Employment-related geographical mobilities in the construction sector: introduction to the special issue. (1st October 2020) - Haan, Michael; Neis, Barbara; Barber, Lachlan; Power, Nicole
ABSTRACT: This introduction serves several purposes. First, it provides some context around the phenomenon of Employment-Related Geographical Mobility. Second, it introduces the papers included in this Special Issue.